(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article considers the lexical language play in American humorous discourse. The research was based on the 1st, 6th, 7th and 8th seasons of the world-famous American sitcoms “Friends” and “The Big Bang Theory”. The author begins by considering the concept of humorous discourse and its characteristic features. In this article humorous discourse is understood as text immersed in a situation of laughter. Humorous discourse is impossible without language play, which is viewed as a certain type of speech behavior of speakers based on a deliberate violation of the system norms of language. There are different types of language play, for example, lexical language play, phonetic language play, word-formation language play, syntactic language play and etc. The author gives the general analysis of the language play in the indicated seasons of these sitcoms. The author considers the lexical language play and gives the examples of the lexical language play from seasons 1, 6, 7 and 8 of the sitcoms “Friends” and “The Big Bang Theory”. The author draws the conclusions on the frequency of lexical language means as a way to achieve a humorous effect.